Three new tubificine species (Annelida: Clitellata: Naididae) from Japan - Ohtaka, Akifumi (Zootaxa, 2024)
Three new species of Tubificinae (Oligochaeta: Naididae), Aulodrilus penicillatus sp. nov., Haber subnivalis sp. nov. and Varichaetadrilus salinus sp. nov. are described from Japanese inland waters. Aulodrilus penicillatus is unique in the genus in having tufts of fine bristles in the position of upper teeth on the chaetae. Haber subnivalis resembles the Baikalian H. vetus (Semernoy) in sharing long and hispid hairs and pectinate chaetae in dorsal bundles. However, H. subnivalis is different from H. vetus in retaining pectinate chaetae throughout the segments, and in the absence of a thick basal membrane around the penes. Varichaetadrilus salinus resembles V. psammophilus (Loden), V. fulleri Brinkhurst & Kathman and V. angustipenis (Brinkhurst & Cook) in having only bifid chaetae in dorsal bundles, but is distinguished from these congeners by having fewer number of chaetae in dorsal bundles, short upper teeth in the dorsal chaetae, and finger cot-shaped penial sheaths. In addition, V. salinus is unique among congeners in the absence of spermathecae.